Impacts of terrain attributes on economics and the environment: costs of reducing potential nitrogen pollution in wheat production. (March 2017) - Walters, Cory G.; Shumway, C. Richard; Huggins, David R.
Abstract: The economic cost of achieving desired environmental outcomes from uniform and variable rate fertilizer application technologies depends both on market forces and agronomic properties. Using spatial econometric methods, we analyze the impact of nitrogen fertilizer supply by terrain attribute on the yield and protein content of hard red spring wheat grown in Eastern Washington as well as the impact on residual nitrogen. We find significant association with all three. The economic impact of nitrogen restrictions depends critically on both prices and level of the restriction. Uniform application of nitrogen was found to economically outperform variable rate application, but variable rate application provided positive environmental benefits due to less residual nitrogen.